Characterization of jackfruit (Artocarpus heterophyllus) waste pectin as influenced by various extraction conditions - Begum, R.; Aziz, Mohammad Gulzarul; Uddin, M. B.; Yusof, Yus Aniza (Elsevier, 2014)
Pectin was extracted from jackfruit (Artocarpus heterophyllus) waste using three different extraction conditions to assess its potentiality as an alternative source of commercial pectin. Jackfruit waste was treated separately with ammonium oxalate, dilute sulphuric acid and sodium hexametaphosphate. The pectin obtained from these methods was compared in terms of yield, physicochemical properties and chemical structure. Among the three solvents, extraction with sodium hexametaphosphate gave the highest yield, however it contained high ash and showed the lowest solubility. Fourier transform infrared spectroscopy of jackfruit waste pectin irrespective of extraction condition revealed a similar surface structure to commercial pectin.